MAPPING OF UMKM WITH WEB-BASED GIS IN CIREBON CITY - Adiyatna, Adiyatna; Maksudi, Maksudi; Sugiyanto, Sugiyanto (Program Studi Teknik Informatika Universitas Muhammadiyah Cirebon, 2025)
Abstract UMKM is one of the industries that supports economic growth in Cirebon City. However, the current condition is that the existence and location of UMKM are difficult for the general public to reach due to the lack of information about the UMKM center itself. Based on these problems, it is necessary to develop an information system for the location of UMKM in Cirebon City to make it easier for the general public to find and know the location of the targeted industry. The system created is implemented in the form of a web-based GIS. In its application, web-based GIS is a digital mapping application that is used to publish data and the location of an object that can be accessed via the web online. The method used in developing this system is the UML method where this method is widely used to visualize and document the software design of a system. The results of this study are in the form of a geographic information system about the location of UMKM centers in Cirebon City that has been successfully built. Keywords: Geographic Information System, UML, DKUKMPP Cirebon City, WebGIS